Piloting of an e-learning programme on children's palliative care. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Downing, Julia; Marston, Joan; Boucher, Sue
Abstract : Background: The International Children's Palliative Care Network (ICPCN) has recognised the need to make training on children's palliative care (CPC) accessible and affordable to all who need it. A recent survey on the availability of CPC training internationally, demonstrated a lack of training in many parts of the world. Thus ICPCN developed a pilot e-learning programme to look at the feasibility of ICPCN using elearning for CPC. Method: An e-learning programme was developed on pain assessment and management that links to new WHO guidelines for persisting pain in children due to be launched later 2011/early 2012. Articulate software was purchased along with a subscription to a Learning Management System (LMS), Articulate online. The programme is aimed at doctors, clinical officers and nurses. Following a brief introduction to the programme, there are discrete modules addressing palliative care in children, pain in children, pain assessment, pain management and the new WHO guidelines. Some resources and a glossary of terms has been included and there is a multiple choice assessment for students to complete. Students are encouraged to undertake a clinical placement, and placement guidelines are provided. Participants have been invited to undertake the programme from four different countries, including Argentina, Romania, Uganda and America. Notice about the programme has also been put up on the ICPCN website. An evaluation form will be completed by all participants. Results: Recruitment for the programme is currently on-going, and the pilot is due to finish by the end of 2011. Results: of the piloting will be shared along with implications for future training developments. Conclusion: The need for training on CPC is great, and there is demand from many different parts of the world for training. In order for CPC training to be accessible and affordable, elearning courses need to promoted and developed where appropriate.